Body Image and Generalized Contentment among Students - Bushra Hassan, Subaita Zubair, Muhammad Naveed Riaz, Sadaf Tariq (Pakistan Journal of Psychology, 2012)
Societal pressures of thinness have assigned worth to the ideal body, contributing to body and life dissatisfaction. The present study is aimed to explore the relationship between body image and generalized contentment among college and university students. The sample consisted of 176 college and university students (M=50; F=126). The age range of the sample was 16-21 years. Multidimensional Body-Self Relations Questionnaire Appearance Scale (MBSRQ-AS; Cash, 2000), and Generalized Contentment Scale (GCS; Hudson, 1982) were used to assess the variables of the study. The Body image satisfaction and generalized life contentment were found positively correlated. The correlation of subscales of appearance evaluation, body areas satisfaction and appearance orientation were positively correlated with the generalized contentment. Negative correlation was found between the subscales of over-weight preoccupation and self-classified weight with generalized contentment. Gender difference in the mean scores on body areas satisfaction scale and appearance evaluation proves that male are more satisfied with their body area and appearance than females.